The Intellectual Climate of Cassius Dio : Greek and Roman Pasts - Bailey, Colin; Poletti, Beatrice; Kemezis, Adam (Historiography of Rome and Its Empire, 2022)
Cassius Dio (c. 160-c. 230) is a familiar name to Roman historians, but still an enigmatic one. His text has shaped our understanding of his own period and earlier eras, but basic questions remain about his Greek and Roman cultural identities and his literary and intellectual influences. Contributors to this volume read Dio against different backgrounds including the politics of the Severan court, the cultural milieu of the Second Sophistic and Roman traditions of historiography and political theory. Dio emerges as not just a recounter of events, but a representative of his times in all their complexity.